2016
DOI: 10.1016/j.bbr.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Forelimb training drives transient map reorganization in ipsilateral motor cortex

Abstract: Skilled motor training results in reorganization of contralateral motor cortex movement representations. The ipsilateral motor cortex is believed to play a role in skilled motor control, but little is known about how training influences reorganization of ipsilateral motor representations of the trained limb. To determine whether training results in reorganization of ipsilateral motor cortex maps, rats were trained to perform the isometric pull task, an automated motor task that requires skilled forelimb use. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…Intriguingly, non-paced strength training had no effect on CSE or SICI. This finding is consistent with previous studies, whereby skilled motor training leads to the functional reorganization of movement representation maps in contralateral M1 and the ipsilateral M1 (Pruitt et al 2016), but is absent following repetitive unskilled motor training (Kleim et al 1998;Plautz et al 2000;Carroll et al 2002). Therefore, the ipsilateral corticospinal adaptations to unilateral visuomotor training and slow-paced strength training are distinct to that of non-paced strength training, despite no differences in the extent of the cross-education effect.…”
Section: The Cortical Adaptations To Cross-education Are Dependent Upsupporting
confidence: 92%
See 2 more Smart Citations
“…Intriguingly, non-paced strength training had no effect on CSE or SICI. This finding is consistent with previous studies, whereby skilled motor training leads to the functional reorganization of movement representation maps in contralateral M1 and the ipsilateral M1 (Pruitt et al 2016), but is absent following repetitive unskilled motor training (Kleim et al 1998;Plautz et al 2000;Carroll et al 2002). Therefore, the ipsilateral corticospinal adaptations to unilateral visuomotor training and slow-paced strength training are distinct to that of non-paced strength training, despite no differences in the extent of the cross-education effect.…”
Section: The Cortical Adaptations To Cross-education Are Dependent Upsupporting
confidence: 92%
“…In the context of cross-education and bilateral transfer, several acute studies that have used TMS have shown increased CSE (Muellbacher et al 2000;Hortobágyi et al 2003;Perez and Cohen 2008;Howatson et al 2011;Frazer et al 2017), decreased SICI (Perez and Cohen 2008;Leung et al 2015), and decreased interhemispheric inhibition (IHI) (Perez and Cohen 2008;Howatson et al 2011) in the iM1. While some structural changes occur within several motor areas (Ruddy et al 2017;Pruitt et al 2016), experimental findings from chronic cross-education studies support a mixture of increased CSE (Hendy et al 2015;Kidgell et al 2011;Kidgell et al 2015) and a decrease in cortical inhibition (SICI, IHI and silent period duration) (Hortobágyi et al 2011;Hendy et al 2012;Kidgell et al 2015;Coombs et al 2016;Mason et al 2017) in the neural structures innervating the untrained limb.…”
Section: The Cortical Adaptations To Cross-education Are Dependent Upmentioning
confidence: 98%
See 1 more Smart Citation
“…1C). 25 Rats were anesthetized with a cocktail of ketamine hydrochloride (50 mg/kg), xylazine (20 mg/kg), and acepromazine (5 mg/kg) injected intramuscularly, and given supplemental doses as needed.…”
Section: Icms Proceduresmentioning
confidence: 99%
“…The maximum stimulation intensity was chosen based on previous studies that indicate ipsilateral motor responses are evoked at higher currents than contralateral responses. 25,32,33 The presence of ipsilateral forelimb movement was first determined, and the current was then lowered to find the lowest threshold at which ipsilateral movement was reliably evoked. After determining the threshold current for ipsilateral responses, the current was again lowered until a threshold was found for contralateral movement.…”
Section: Icms Proceduresmentioning
confidence: 99%